SCANDINAVIANS AND THE LEAGUE OF NATIONS SECRETARIAT, 1919–1946. Issue 4 (8th August 2019) - Gram-Skjoldager, Karen; Ikonomou, Haakon A.; Kahlert, Torsten
Abstract : This article reintroduces the Scandinavian perspective on interwar internationalism by mapping and analysing the Scandinavian staff in the League Secretariat. Combining quantitative and qualitative sources, the article explores how the Scandinavian members of staff were viewed by and situated in the institutional topography of the League Secretariat; how they were related to and positioned towards the national foreign policy establishment; and what the postwar trajectories of the Scandinavian League staff looked like. With these perspectives, the article offers three key insights: First, the interplay between the League Secretariat and the foreign policy strategies pursued by the Scandinavians, was highly productive, and the international issues that different Scandinavian countries engaged with through the League staff was substantially determined by the institutional set-up of the League. Second, we note clear differences in terms of strategy and commitment between the three countries' Ministries of Foreign Affairs (MFAs). Third, the careers of the Scandinavians working in the Secretariat show a clear continuity of Scandinavian internationalism across the Second World War. The experience, prestige and networks gained from working in the League Secretariat often translated into key positions in postwar IOs or within the new multilateral parts of the MFAs.